Productivity, profitability and trade-offs in organic farming-based agricultural systems: Global trends and role in shaping new agri-food systems - KUMAR, SUNIL; ANSARI, M A; SHARMA, S K; SINGH, RAGHAVENDRA (The Indian Journal of Agricultural Sciences, 2025)
Organic farming is emerging as an alternative sustainable agri-food system globally both in developed and developing nations. In India, organic farming offers a promising alternative to conventional farming and may contribute significantly to mitigate climate change by improving soil health, fostering biodiversity, and enhancing carbon sequestration. Lower yields, higher production costs and market access barriers, particularly for smallholder farmers are significant challenges for scaling up of organic farming practices on small farmers’ fields. However, growing opportunities for premium market prices for organic products, reduced input costs over time and improved soil resilience need to be addressed. This paper examines global and national trends, highlighting India’s position as a major player in the organic food ecosystem with a growing area, organic food products market and organic production technologies. It also delves into the productivity and profitability of organic farming systems, acknowledging the trade- offs between environmental benefits and economic costs. The trade-off is evidenced in terms of long-term ecological advantages such as improved soil structure, nutrient cycling and reduced pesticide residues, thus ensuring healthier food system and sustainable farming practices. Government policies, institutional support and market incentives are crucial in accelerating the adoption of organic practices. For scaling up of organic farming, the role of policy recommendations is also vital and significant to contribute to food security and environmental sustainability. The key to achieving improvements in organic farming is adopting diversification into several different crops for direct human consumption and services for the community. Profitability in the market and promoting demand for products that would improve the sustainability of farm and beyond will increase the food security of the global food system at the farm-level, ultimately leading to greater sustainability and resilience in agri-food systems.